Do Our Universities Need Philosophy? - G. A. Antipov (Высшее образование в России)
Without any allusion to the times when philosophy was an intellectual dominant of university education, there is no way to consider the present stage of philosophy in universities satisfying. It is supplanted to a distant periphery at a modern university and ends up in a deep shadow of science. As it is demonstrated in the article, such a situation results from misunder standing of the essence and perspective of philosophical knowledge, as well as from the dominant position of science in modern culture. Philosophy is a reflection and a “philosophizing”; as it was determined by M. Heidegger, it is an individual’s and cultural identity. As such, it appears as the main form of subject’s identification and adaptation to the changes taking place in the scientific knowledge and in the world in general.